Why Road Maintenance is Important and How to Get it Done - Burningham, Sally (World Bank, Washington, DC, 2012)
Roads, and means of transport, make a crucial contribution to economic development and growth and bring important social benefits. Poorly maintained roads constrain mobility, significantly raise vehicle operating costs, increase accident rates and their associated human and property costs, and aggravate isolation, poverty, poor health, and illiteracy in rural communities. This Note highlights the economic and social importance of regular road maintenance and recommends ways to achieve sustainable road maintenance with scarce public resources. Its audience is not specialists but rather people who need to understand road maintenance enough to discharge their responsibilities effectively: government policy-makers, mayors, ministry staff, new World Bank staff and staff in sectors such as rural development and social funds. The reference section offers sources providing more detailed information.